ADVANCEMENTS IN CYANOTOXIN DETECTION: INNOVATIONS IN EARLY MONITORING TECHNIQUES - Kashmala Ahmad; Rabia Faridi; Bushra Ahmad; Fatima Ahmad; Rabiha Noor; Asmara Saher; Muhammad Kashif Hanif; Namal Rauf; Iman Fatima; Obaid Ullah Khan (Policy Research Journal, 2025)
Cyanobacterial harmful algal blooms (CyanoHABs) threaten global water resources by producing cyanotoxins that harm human and environmental health. Timely and accurate detection of these toxins is essential for effective water quality management and the protection of public health. This review highlights recent advancements in early detection techniques, covering traditional methods like chromatography and ELISA, as well as emerging technologies such as biosensors, molecular diagnostics, and remote sensing. The discussion emphasizes sensitivity, specificity, and speed, alongside their suitability for various water matrices and cyanotoxin types. Integration of multiple methods into robust monitoring strategies, including automated real-time systems and big data-driven early warning frameworks, is explored. Key challenges such as the need for standardized protocols, enhanced sensor technologies, and better understanding of cyanotoxin dynamics are identified. Additionally, the review addresses the influence of climate change on CyanoHABs and its implications for future detection strategies.